Peran Dokter Gigi Dalam Penanganan Berat Badan Berlebih dan Obesitas - I Komang Evan Wijaksana (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2016)
Overweight and obesity has become an epidemic in many developed and developing countries, and its prevalence is increasing globally. Overweight and obesity obesity are associated with many diseases such as cardiovascular diseases, some forms of cancer, type 2 diabetes mellitus and chronic oral diseases. It is important for dentists to understand and recognize overweight and obesity, educate their patients on its associated risks, promote a healthy lifestyle for their patients, and modify any necessary dental treatments and postoperative procedures for overweight and obese patients.  A multidisciplinary approach of overweight and obesity is needed for optimal control. Professional dentist must be prepared to manage the overweight and obesity-related effects of co-morbidities and oral diseases and working in conjunction with other health care providers. However, the majority do not routinely measure weight and height, nor calculate body mass index for comprehensive care patients in their daily dental practice, thus the dentist role in overweight and obesity is rare. The purpose of this article is to review the assessment of overweight and obesity, the relevance of overweight and obesity to oral helath and dental practice, and highlight some of the actions dentist can to prevent and decrease the risk of both these diseases.